2011
DOI: 10.1111/j.1348-0421.2011.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of high-mobility group box 1 protein and twelve other markers in discriminating bacterial, viral and co-infected bronchial pneumonia in Han children

Abstract: Pneumonia in children is common and can lead to grave consequences if not addressed in a proper and timely manner. In the management of pneumonia, early identification of the causative infective agent is of obvious importance for treatment, as it allows selection of the appropriate antibiotics. However, such identification requires laboratory test results, which may not be immediately available. The aim of this study was to evaluate the accuracy and usefulness of 13 markers in differentiating between viral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…Community-acquired pneumonia is pneumonia acquired infectiously from normal social contact, as opposed to being acquired during hospitalization (termed hospital-acquired pneumonia). Increased serum HMGB1 level is caused by bacteria or virus in both community-acquired and hospital-acquired pneumonia (Achouiti et al, 2013; Angus et al, 2007; Entezari et al, 2012; Ito et al, 2011; Kosai et al, 2008; Sharma et al, 2013; Tasaka et al, 2010; van Zoelen et al, 2008; Zhou et al, 2011d). Both RAGE and TLR4 play roles in the regulation of HMGB1-mediated inflammatory response during pneumonia (Achouiti et al, 2013; Entezari et al, 2012; Ramsgaard et al, 2011).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…Community-acquired pneumonia is pneumonia acquired infectiously from normal social contact, as opposed to being acquired during hospitalization (termed hospital-acquired pneumonia). Increased serum HMGB1 level is caused by bacteria or virus in both community-acquired and hospital-acquired pneumonia (Achouiti et al, 2013; Angus et al, 2007; Entezari et al, 2012; Ito et al, 2011; Kosai et al, 2008; Sharma et al, 2013; Tasaka et al, 2010; van Zoelen et al, 2008; Zhou et al, 2011d). Both RAGE and TLR4 play roles in the regulation of HMGB1-mediated inflammatory response during pneumonia (Achouiti et al, 2013; Entezari et al, 2012; Ramsgaard et al, 2011).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…A total of eleven studies involved CRP [14,16,17,19,20,22,23,[25][26][27][28][29]. In all the studies analysing CRP as a diagnostic marker, the average CRP level was higher in the bacterial group than viral group [14,20,22,23,[25][26][27][28][29].…”
Section: Standard Biomarkers In Community-acquired Pneumonia C Reactimentioning
confidence: 99%
“…This meant that before hospital admission, many patients might have had exposure to antibiotics which may have altered the level of CRP [27]. Another drawback was that only one study investigated co-infection (viral-bacterial) and concluded that CRP level did not correlate with co-infection [29].…”
Section: Standard Biomarkers In Community-acquired Pneumonia C Reactimentioning
confidence: 99%
“…20,21,[32][33][34] The optimal cutoff point for hs-CRP was 1.53 mg/dl (sensitivity 90%, specificity 56%), and the AUC for hs-CRP was 0.772, indicating this diagnostic value was valid. Although some authors were arguing that CRP is not useful in distinguishing coin-fected bacterial infections in patients with Rhinovirus community pneumonia, 26,35 other studies were confirming the ability to distinguish between viral and bacterial agents that cause pneumonia with CRP limit point > 0.8mg/dl. [36][37][38] Although controversies exist surrounding the use of the hs-CRP index to identify severe pneumonia caused by coinfection with the virus, this biomarker can still be used to support decisions about antibiotic use.…”
Section: Discussionmentioning
confidence: 99%